Rheumatoid polyarthritis after rubella. Issue 3 (June 1978) - McCormick, J N; Duthie, J J; Gerber, H; Hart, H; Baker, S; Marmion, B P
Abstract : A 21-year-old woman developed persistent polyarthritis indistinguishable from rheumatoid arthritis after rubella. The arthritis persisted for approximately 30 months and was associated with high levels of antibody to rubella virus and with rheumatoid factor. The antibody titres declined pari passu with clinical improvement which progressed to complete resolution. Fractionation of serial serum specimens showed a substantial and persistent IgM antibody response to rubella virus. Rubella antigen was not demonstrated in the synovial exudate.